Relationship of white matter hyperintensities with clinical features of seizures in patients with epilepsy - USLU, Ferda Ilgen; ÇETINTAŞ, Elif; YURTSEVEN, İsmail; ALKAN, Alpay; KOLUKISA, Mehmet (Arquivos de Neuro-Psiquiatria, 2021)
Background: Although epilepsy is primarily known as a cortical disorder, there is growing body of research demonstrating white matter alterations in patients with epilepsy. Objective: To investigate the prevalence of white matter hyperintensities (WMH) and its association with seizure characteristics in patients with epilepsy. Methods: The prevalence of WMH in 94 patients with epilepsy and 41 healthy controls were compared. Within the patient sample, the relationship between the presence of WMH and type of epilepsy, frequency of seizures, duration of disease and the number of antiepileptic medications were investigated. Results: The mean age and sex were not different between patients and healthy controls (p>0.2). WMH was present in 27.7% of patients and in 14.6% of healthy controls. Diagnosis of epilepsy was independently associated with the presence of WMH (ß=3.09, 95%CI 1.06-9.0, p=0.039). Patients with focal epilepsy had higher prevalence of WMH (35.5%) than patients with generalized epilepsy (14.7%). The presence of WMH was associated with older age but not with seizure characteristics. Conclusions: WMH is more common in patients with focal epilepsy than healthy controls. The presence of WMH is associated with older age, but not with seizure characteristics.
Keywords: Epilepsy; White Matter; Epilepsies, Partial; Epilepsy, Generalized